Description of sedentary lifestyle in patients with cardiovascular disease during the Covid-19 pandemic - Jon Hafan Sutawardana; Yustika Dian Pawesti; Murtaqib Murtaqib (Universitas Muhammadiyah Semarang, 2022)
A sedentary lifestyle is any type of activity that only expends a small amount of energy with an energy expenditure of not more than 1.5 METs when sitting or lying down. this has a very bad impact on health. These activities have a very bad impact on health. During the COVID-19 pandemic, people face many big challenges, one of which is social distancing in a sedentary lifestyle. The objective of this study is to describe changes in sedentary lifestyles among cardiovascular disease patients during the COVID-19 pandemic. The research design used was a literature review using 3 databases (Pubmed, Proquest, and Science Direct). The process of searching for articles using keywords and Boolean operators (AND, OR, or NOT) aims to define and expand the literature. The review found that the sedentary lifestyle increased up to 8 hours/day. In addition to what has been mentioned 4 other articles also mention an increase in sedentary lifestyle time and an increase in sitting time, this is in accordance with research conducted on the average daily duration of sedentary behaviour is 8.3 hours between Koreans and 7, 7 hours among American adults due to government regulations during the pandemic. All articles show that people who tend to be older and male have a higher risk of developing cardiovascular cases that lead to death during the COVID-19 pandemic. So it is necessary to expand the scope of information about the importance of physical activity so that all people with cardiovascular disease have high vigilance.